Sosialisasi Aplikasi Statistika Pada Evaluasi Hasil Belajar Siswa Berbantuan Microsoft Excel Pada Guru SMPN 1 Gerung - Nyoman Sridana; Amrullah Amrullah; Hapipi Hapipi; Deni Hamdani; Nourma Pramestie Wulandari (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
This service is based on the competency standard of statistical knowledge and the evaluation of teachers is still low, so socialization is needed to teachers regarding the application of statistics to analyze data on evaluating students’ learning outcomes. Professional teachers should always try to improve their knowledge in the field of teaching matherials and pedagogics. The method used in this service activity is mentoring offline and online (including lectures, question-and-answer, assigntments, and presentations method). This service activity is arranged in four stages, where one stage is carried out online and three stages are carried out online. Offline activities are carried out using lecture and question-and-answer methods, while onine activities are carried out with FGD, question-and-answer, and presentations method. The expected output of this service activity is that the teachers are proficient in using statistical application programs in analyzing valid and significant evaluation data of students’ learning outcomes.